2022
DOI: 10.48550/arxiv.2205.13174
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optical appearance of Einstein-Æther black hole surrounded by thin disk

Abstract: In Einstein-AEther theory, the Lorentz symmetry is locally broken in the high-energy regime due to the presence of the AEther field. This shall leave significant imprint on astronomical observation. In this paper, we investigate the optical appearance of two types of the static and spherically symmetric black holes in Einstein-AEther theory. Via Euler-Lagrange equation, we obtain the equations of motion of the photon and calculate the total deflection angle of the photon trajectory around the black hole. By cl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Faraji et al in their recent paper confirmed that the quadrupole parameter plays a non-negligible role in the physical properties of the thin disk solution around twisted Schwarzschild spacetime [54]. Recently, efforts have been devoted to studying the shadows and the observational appearance of black holes which are surrounded by spherically symmetric accretion and thin disk accretion [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Considering both the static and infalling spherically symmetric accretion models, the inner region of the infalling one is darker than that of the static one due to the Doppler effect [23,24].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Faraji et al in their recent paper confirmed that the quadrupole parameter plays a non-negligible role in the physical properties of the thin disk solution around twisted Schwarzschild spacetime [54]. Recently, efforts have been devoted to studying the shadows and the observational appearance of black holes which are surrounded by spherically symmetric accretion and thin disk accretion [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Considering both the static and infalling spherically symmetric accretion models, the inner region of the infalling one is darker than that of the static one due to the Doppler effect [23,24].…”
Section: Introductionmentioning
confidence: 98%
“…Considering both the static and infalling spherically symmetric accretion models, the inner region of the infalling one is darker than that of the static one due to the Doppler effect [23,24]. Also, under the background that black holes are surrounded by the thin disk accretion, the light rays around black holes can be divided into three types, i.e., direct emission, lens ring and photon ring [23,24,27,30,[32][33][34][35][36]. Moreover, there are differences in the contributions of direct emission, lens rings and photon rings to the observed intensity of black holes.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, they also showed that the luminosities of both the shadows and rings of the Hayward BH are affected by the accretion flow property and the BH magnetic charge [28]. The BH shadow characteristics in the various gravity are also investigated in [29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%